1997
DOI: 10.1002/chin.199726281
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Aluminum Metallization Using a Combination of Chemical Vapor Deposition and Sputtering.

Abstract: Aluminum Metallization Using a Combination of Chemical Vapor Deposition and Sputtering.-A combination process meeting the requirements for ULSI (ultralarge scale integration) interconnections and being promising for the manufacturing of subhalf micron multilevel interconnections for ULSI comprises hole filling by CVD of Al from Me2AlH onto TiN followed by film thickening by Al alloy sputtering. Via holes with a diameter of 0. 3 µm and an aspect ratio of 2.7 are successfully filled at 130 . degree.C. Contact re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Thus, an increment in the density of nuclei is believed to be a key factor for the resolution of the problem of rough-surfaced CVD Al films. 5,[8][9][10]17 DMEAA is known to deposit Al films readily on most metallic surfaces, but not on dielectrics such as SiO 2 and Si 3 N 4 . Interestingly, it was also reported that Al films could be formed on various metal surfaces coated with native metal oxide layers.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, an increment in the density of nuclei is believed to be a key factor for the resolution of the problem of rough-surfaced CVD Al films. 5,[8][9][10]17 DMEAA is known to deposit Al films readily on most metallic surfaces, but not on dielectrics such as SiO 2 and Si 3 N 4 . Interestingly, it was also reported that Al films could be formed on various metal surfaces coated with native metal oxide layers.…”
Section: Resultsmentioning
confidence: 99%
“…There are various source chemicals for CVD aluminum, such as trimethylaluminum, 1 triisobutylaluminum (TIBA), [2][3][4][5][6] dimethylaluminum hydride (DMAH), [7][8][9][10] and amine-alane adducts such as trimethylamine alane, 11 triethylamine alane, 12 and dimethylethylamine alane. [13][14][15][16][17] Among these precursors, dimethylethylamine alane (DMEAA) is considered to be the most promising precursor for Al CVD due to the absence of carbon contamination in its deposits, its high vapor pressure, and low deposition temperature; it also has the additional advantage of being liquid.…”
mentioning
confidence: 99%
See 3 more Smart Citations